Diagnostic Accuracy of Urine Dipsticks for Urinary Tract Infection Diagnosis during Pregnancy: A Retrospective Cohort Study - Dominique E. Werter; Caroline Schneeberger; Suzanne E. Geerlings; Christianne J. M. de Groot; Eva Pajkrt; Brenda M. Kazemier (MDPI AG, 2024)
Objective: Urinary tract infections (UTIs) represent the most prevalent infections among pregnant women. Many pregnant women experience frequent voiding or lower abdominal pain during pregnancy due to physiologic changes. Due to the possible consequences of a UTI in pregnancy, pregnant women are more often tested for UTIs. This study aimed to assess the diagnostic accuracy of dipsticks in diagnosing UTIs in pregnant women while using the urine culture as the reference standard. Study design: This was a retrospective cohort study, conducted at two academic hospitals in the Netherlands among pregnant women. Pseudonymized data were collected from patient files. The results of the urine dipstick and the urine culture in pregnant women were linked. Additionally, nitrofurantoin prescriptions were linked to culture results. A positive urine culture was considered the reference test for a UTI. Results: Between 1 January 2017 and 28 February 2021, a total of 718 urine samples with leukocyte esterase dipstick results within 24 h of the urine culture were analyzed. Of these samples, a nitrite dipstick result was also available in 337 cases. Only 6.8% of the 718 urine samples yielded positive cultures. The sensitivity and specificity of leukocyte esterase were 75.5% and 40.4%, respectively; for nitrite, 72.0% sensitivity and 73.4% specificity were found. When at least one of the two tests was positive, the sensitivity and specificity were 92.0% and 27.9%, respectively. When both tests were positive, the sensitivity and specificity were 52.0% and 82.7%, respectively. In only 16.8% of the women to whom nitrofurantoin was prescribed, the urine cultures returned positive using a cut-off of 105 colony forming units/mL. Conclusion: The diagnostic performance of leukocyte esterase, nitrite, or their combination in clinical practice is lower than previously reported in study settings among pregnant women. A significant proportion of women treated with nitrofurantoin were found to have no UTI, suggesting potential over-prescription based on dipstick test results. Healthcare providers should be aware of this reduced performance in clinical practice and carefully weigh the risks of antibiotic treatment by suspicion of a UTI against the possibility of delayed treatment awaiting culture results in individual patients.